Validitas Media Diorama Siklus Air Upaya Meningkatkan Hasil Belajar IPA di SD 5 Klaling - Silfia, Icha; M. Ali Shodiqin; Syifa’ul Azzhar; Sekar Dwi Ardiyanti (Universitas Palangka Raya, 2023)
The purpose of this study was to determine the feasibility of science mutant water cycle diorama media for fifth grade students of SD 5 Klaling. This research uses the Research and Development (RnD) method. The research was carried out through several stages, namely potential and problem identification, data collection, product design, media validation and media revision. Data collection techniques in this study were through interviews, questionnaires and documentation. The results of this study were that the developed media was declared feasible by media expert validation, namely by the overall average of 27 and percentage of 81% with the appropriate category, material expert validation was average - overall average of 4.1 and a percentage of 82% with a feasible category for testing. Based on the research results obtained, the conclusion from the development of water cycle diorama learning media is said to be feasible in science learning with water cycle material in class V SD 5 Klaling.